Participation in faecal immunochemical testing-based colorectal cancer screening programmes in the northwest of Europe. (June 2020) - Toes-Zoutendijk, Esther; Portillo, Isabel; Hoeck, Sarah; de Brabander, Isabel; Perrin, Philippe; Dubois, Catherine; van Leerdam, Monique; Lansdorp-Vogelaar, Iris; Bardou, Marc
Objective: This study compared the participation in four faecal immunochemical testing-based screening programmes for colorectal cancer in Flanders, France, Basque country and the Netherlands, to identify factors to further optimize faecal immunochemical testing programmes. Method: Background information and data on performance indicators were collected and compared for the four programmes. Results: Invitation method, reminders, funding, faecal immunochemical testing cut-off and follow-up after positive faecal immunochemical testing differed in the four programmes. In France, only an invitation letter is sent by mail, while the sample kit must be collected from the general practitioner. In the other programmes, an invitation letter including the sample kit is sent by mail. Participation rates vary substantially according to the method of invitation, with the highest participation rates in the Netherlands (73.0%) and Basque country (72.4%), followed by Flanders (54.5%) and France (28.6%). Basque country (92.8%) and France (88.4%), the two programmes with most active involvement of general practitioners in referral for colonoscopy, had the highest participation rates for colonoscopy. Conclusions: Large differences in screening participation observed between programmes according to the invitation method used suggest that changes to the design of the programme, such as including the sample kit with the invitation, or active involvement of GPs, might increase participation.